Understanding the Battle for Universal Pharmacare in Canada; Comment on "Universal Pharmacare in Canada" - Marc-André Gagnon (Kerman University of Medical Sciences, 2021)
Drug coverage in Canada is a patchwork; an inequitable inefficient and unsustainable patchwork with no coherence or purpose. Some people think that we can solve the problem by adding more patches, but the core of the problem is that it is a patchwork. For the working population, access to medicines is still organized as privileges offered by employers to their employees. Universal pharmacare would not only provide better access to needed prescription drugs, but also eliminate waste, ensure value-for-money and help improve drug safety and appropriate prescribing. Opponents fear that a universal pharmacare plan would ration drugs, and impede drug access for some patients. However, these claims misunderstand the reality of drug coverage, pricing and access. Opponents propose, instead, to "fill the gap" of current drug coverage by implementing catastrophic coverage, which would serve commercial interests without maximizing health outcomes for the Canadian population. In spite of overwhelming evidence and consensus in the academic community in favour of universal pharmacare, the battle is far from over.